Pharmacogenotyping of CYP3A5 in predicting dose-adjusted trough levels of tacrolimus among Malaysian kidney-transplant patients - Hamzah, Sharina; Teh, Lay Kek; Shia, John Kwong Siew; Ahmad, Ghazali; Wong, Hin Seng; Zakaria, Zainul Amiruddin; Salleh, Mohd Zaki (NRC Research Press, 2014)
Tacrolimus (FK506) is a calcineurin inhibitor with a narrow therapeutic index that exhibits large interindividual variation. Seventy-eight kidney transplant patients treated with tacrolimus were recruited to study the correlation of dose adjusted trough level (level/dose; L/D) of tacrolimus with CYP3A5 and ABCB1 genotypes, as well as the mRNA copy number of ABCB1 in blood. Patients were genotyped for ABCB1 (C1236T, G2677T/A, and C3435T) and CYP3A5 (G6986A), while ABCB1 mRNA transcript copy number was determined by absolute quantification (real-time PCR) in 46 patients. CYP3A5*3 genotypes were found to be a good predictor of tacrolimus L/D in kidney-transplant patients. Significantly higher L/D was observed among non-expressors (2.85, 95%: 2.05-3.70 (ng·mL(-1))/(mg·kg(-1))) as compared with the expressors (1.15, 95%: 0.95-1.80 (ng·mL(-1))/(mg·kg(-1))) of CYP3A5 (Mann-Whitney U test; P < 0.001). No correlation was observed between L/D and the ABCB1 genotypes. A significant inverse correlation of blood ABCB1 mRNA level with L/D was demonstrated (Spearman's Rank Order correlation; P = 0.016, rs = -0.348). However, in multiple regression analysis, only CYP3A5*3 genotype groups were found to be significantly correlated with tacrolimus L/D (P < 0.001). These findings highlight the importance of CYP3A5*3 pharmacogenotyping among kidney-transplant patients treated with tacrolimus, and confirm the role of blood cell P-glycoprotein in influencing the L/D for tacrolimus.